THE CONDITIONS OF FORMING ACTIONS WITH SUBJECTS AND MATERIALS IN EARLY CHILDHOOD - Pradun, Inna; Shlat, Natalia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The article deals with the problem of forming of actions with subjects and materials in early childhood: significance of subject activity for child's development, features of creating of developing object–spatial environment in a group of young children, pedagogical conditions for effective formation of actions with subjects and materials.The article describes an empirical study of the state of development of subject activity in early childhood: diagnostic tools are characterized, the results of the parameters proposed by the authors are analyzed. The authors diagnose the quality of equipment of modern developing environment and professional readiness of teachers to create conditions for the effective formation of children's actions with subjects and materials.